1986
DOI: 10.1139/x86-209
|View full text |Cite
|
Sign up to set email alerts
|

Postfire survival in Douglas-fir and lodgepole pine: comparing the effects of crown and bole damage

Abstract: Survival patterns after late summer wildfires were evaluated for Douglas-fir and lodgepole pine in the northern Rocky Mountains. Crown scorch was the most important variable for predicting postfire survival and variables representing bole damage improved the significance of logistic regression models for both species. Crown scorch and basal scorch were the best combination of variables for predicting survival in lodgepole pine. Crown scorch and insect damage were the best combination of variables for predictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 0 publications
4
38
0
Order By: Relevance
“…and ponderosa pine appears to be weak Safranyik et al 2001;Elkin and Reid 2004), although successful attack and reproduction have been observed in lodgepole pine with moderate fire injury (Geiszler et al 1984). The Douglas-fir beetle has been consistently associated with fire-injured trees, often attacking larger trees with moderate to high levels of basal bole injury (Furniss 1965;Rasmussen et al 1996;Weatherby et al 2001) and light to moderate levels of crown injury (Peterson and Arbaugh 1986;Ryan and Amman 1994;Weatherby et al 2001;Cunningham et al 2005), with attacks declining only in completely defoliated trees (Furniss 1965).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and ponderosa pine appears to be weak Safranyik et al 2001;Elkin and Reid 2004), although successful attack and reproduction have been observed in lodgepole pine with moderate fire injury (Geiszler et al 1984). The Douglas-fir beetle has been consistently associated with fire-injured trees, often attacking larger trees with moderate to high levels of basal bole injury (Furniss 1965;Rasmussen et al 1996;Weatherby et al 2001) and light to moderate levels of crown injury (Peterson and Arbaugh 1986;Ryan and Amman 1994;Weatherby et al 2001;Cunningham et al 2005), with attacks declining only in completely defoliated trees (Furniss 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Tree size and heat-caused crown and cambium injury have been found to be the most significant factors for predicting tree mortality following fire, with the levels varying among tree species (Wagener 1961;. Several studies also attributed observed bark beetle attacks after fire to an increase in delayed tree mortality (Peterson and Arbaugh 1986;Bradley and Tueller 2001;. Using data from a wildfire in Utah, Cunningham et al (2005) correlated fire-injury variables with Douglas-fir beetle attack.…”
Section: Introductionmentioning
confidence: 99%
“…A study of Douglas-fir survival after fire that included sampling in northern Idaho showed that crown scorch was the most useful predictor of mortality (Peterson and Arbaugh 1986), but many other factors were important. Crown scorch from summer fires may be more damaging than from fires late in the season.…”
Section: Relativementioning
confidence: 99%
“…In a study that included samples from northern Idaho, Peterson and Arbaugh (1986) found that crown scorch and basal scorch were the best predictors of mortality. Trees that survive low-severity fires do not usually show increased growth rates.…”
Section: Lodgepole Pine (Pinus Contorta)mentioning
confidence: 99%
“…Hood (2007) predicted mortality using percent crown length kill and cambium kill in all optimal models for Douglas-fir. Fowler (2004) stated that crown scorch volume were clearly the best crown damage measurement to predict post fire mortality of Douglas-fir, citing Peterson (1984 and1985), Peterson and Arbaugh (1986and 1989), and Ryan et al (1988. However, Ryan et al (1988) reported that cambial death measured directly was a better predictor of Douglas-fir tree mortality than crown scorching.…”
Section: Leaves and Needles (Ln)mentioning
confidence: 99%